Malaysian case law on issues of Islamic home finance Bay' Bithaman Al-Ajil (BBA): An Analysis - Md Dahlan, Nuarrual Hilal; Shuib, Mohd Sollehudin; Mohd Noor, Fauziah (Global Academic Excellence, 2018)
Islamic Banking has been established since in the 1980s in Malaysia. Various Islamic Home Finance products have been introduced and practised in Malaysia. However, these products have been tainted with the issue of their inadequacy to deal with the issues of problematic housing projects such as late delivery of vacant possession, shoddy workmanship and failure of the developer to comply with the sale and purchase agreements. This paper aims to study the case law dealing with issues, other than issues of abandoned housing projects, in Islamic Home Finance involving Islamic Home Finance Bay’ Bithaman Al-Ajil (BBA). This paper used shariah (Islamic Law), legal doctrinal, qualitative social and textual analysis research methodologies. This paper finds that the case law reveals weaknesses of the BBA. The outcome of this paper will improve the theory and practice of Islamic Home Finance BBA in Malaysia.